Method for reducing chromate electrolysis energy consumption
By adding electrolytic additives such as sodium oleate, thiourea and hydrochloric acid to the chromate electrolyte, the problem of high energy consumption in the preparation of metal chromium by chromate electrolytics is solved, and energy consumption is reduced and production efficiency is improved.
Patent Information
- Application Number
- CN202411978148.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The high energy consumption in the preparation of metal chromium by chromate electrolysis leads to an increase in production costs, limiting its application in large-scale industrial production.
Add electrolytic additives such as sodium oleate, thiourea and hydrochloric acid to the chromate electrolyte to reduce current oscillation and thus reduce energy consumption.
By introducing electrolytic additives, the current oscillation is effectively reduced, energy consumption is reduced, the efficiency of electrolytic preparation of metal chromium is improved, the production cost is reduced, and the negative impact on the environment is reduced.
Smart Images

Figure CN119800444A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a method for reducing energy consumption of chromate electrolysis. Background Art
[0002] Chromium metal has been widely used in the metallurgical industry due to its excellent properties such as high hardness, wear resistance, heat resistance and corrosion resistance. In addition to the production and application of traditional stainless steel and alloy steel, it is also widely used in high-end fields such as aerospace, electronics, automobiles, and energy. The process of preparing chromium metal by chromate electrolysis started early. With the improvement of the purity requirements of chromium metal and the advancement of metallurgical technology, this process has gradually received attention. Although the early electrolysis process was relatively simple in terms of technology and equipment, and had problems such as low current efficiency, high energy consumption, and limited production scale, it laid the foundation for subsequent technological innovation. With the continuous advancement of technology, the production scale of chromium metal by chromate electrolysis has gradually expanded to meet the growing demand for chromium metal in the metallurgical industry. Some large metallurgical enterprises have adopted advanced electrolysis equipment and processes to achieve large-scale production of chromium metal, improving production efficiency and economic benefits.
[0003] However, the high energy consumption in the process of electrolytic preparation of metallic chromium leads to increased production costs, which to a certain extent limits its application in large-scale industrial production. From a theoretical perspective, the electricity consumption for preparing one ton of hexavalent chromium into metallic chromium is about 15,000 kWh. However, in the actual industrial production process, the situation is quite different. The electricity consumption for preparing one ton of metallic chromium is as high as 41,000-42,000 kWh. In-depth exploration of the root cause revealed that the current efficiency of the process is at an extremely low level of only 21%. Such a low current efficiency directly leads to high energy consumption in industrial electrolytic chromium, which not only increases production costs, but also causes huge waste of energy. This has become the main obstacle to the development of electrolytic chromium technology, and an effective solution is urgently needed to break through this dilemma. Summary of the invention
[0004] The object of the present invention is to provide a method for reducing the energy consumption of chromate electrolysis, so as to solve the technical problem of high energy consumption in the existing process of preparing metallic chromium by chromate electrolysis.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for reducing energy consumption of chromate electrolysis comprises the following steps:
[0007] Electrolytic additives are added to the chromate electrolyte, and then metallic chromium is prepared by electrolysis. The introduction of the electrolytic additives can reduce the energy consumption caused by current oscillation, thereby reducing the overall energy consumption of chromate electrolysis.
[0008] According to the above technical means, by adding electrolytic additives to the chromate electrolyte, current oscillation can be effectively reduced, thereby reducing energy consumption. Current oscillation is a common phenomenon in the electrolysis process, which will lead to an increase in energy consumption and a decrease in electrolysis efficiency. The introduction of electrolytic additives can stabilize the current, making the electrolysis process more stable, thereby reducing energy consumption. This method can improve the efficiency of electrolytic preparation of metallic chromium. The addition of electrolytic additives can not only reduce energy consumption, but also optimize electrolysis conditions, making the preparation of metallic chromium more efficient. This helps to improve production efficiency and reduce production costs. The method is also environmentally friendly. The traditional chromate electrolysis process may produce some harmful substances and pollute the environment. By introducing electrolytic additives, the emission of harmful substances in the electrolysis process can be reduced, reducing the negative impact on the environment.
[0009] Preferably, the electrolytic additive is selected from at least one of sodium oleate (NaOL), thiourea [SC(NH2)2] and hydrochloric acid (HCl).
[0010] Experimental studies have shown that the use of sodium oleate (NaOL), thiourea [SC(NH2)2] and hydrochloric acid (HCl) as electrolytic additives can effectively reduce the energy consumption caused by anode current oscillation, thereby reducing the overall energy consumption of chromate electrolysis.
[0011] The principles of using sodium oleate (NaOL), thiourea [SC(NH2)2] and hydrochloric acid (HCl) as electrolytic additives to reduce current oscillations are as follows: sodium oleate can be adsorbed on the electrode surface to form a protective film, reducing the active points on the electrode surface, thereby suppressing the disordered fluctuations of the current. Thiourea, as an organic sulfur compound, can form stable complexes with metal ions, reduce the active substances on the electrode surface, and further stabilize the current. Hydrochloric acid optimizes the electrolytic environment by adjusting the pH value of the electrolyte, reducing the reaction activity of the electrode surface, and reducing current oscillations. Among them, the simultaneous addition of two or three additives can also stabilize the current, thereby effectively reducing energy consumption and improving the efficiency of electrolytic preparation of metallic chromium.
[0012] Preferably, the amount of sodium oleate (NaOL) added to the chromate electrolyte is 13-200 mg / L.
[0013] By precisely controlling the amount of sodium oleate (NaOL) added to the chromate electrolyte, not only can the energy consumption caused by the oscillation of the anode current be effectively reduced, but the current efficiency and voltage stability during the electrolysis process can also be effectively improved, making the electrolysis process more stable and improving the electrolysis efficiency. Moreover, as an environmentally friendly additive, sodium oleate can also reduce the emission of harmful substances, meeting the requirements of green production.
[0014] Preferably, the amount of sodium oleate (NaOL) added to the chromate electrolyte is 200 mg / L.
[0015] Preferably, the amount of thiourea [SC(NH2)2] added to the chromate electrolyte is 18 to 350 mg / L.
[0016] Preferably, the amount of thiourea [SC(NH2)2] added to the chromate electrolyte is 34 mg / L.
[0017] Preferably, the amount of hydrochloric acid (HCl) added to the chromate electrolyte is 0.2-4 g / L.
[0018] By precisely controlling the amount of hydrochloric acid (HCl) added to the chromate electrolyte, not only can the energy consumption caused by the oscillation of the anode current be effectively reduced, but the precipitation and deposition of metal ions during the electrolysis process can also be effectively promoted, optimizing the quality and performance of the electrolysis products. The addition of hydrochloric acid can also help remove impurities and oxides in the electrolyte, improve the purity of the electrolyte, and thus reduce the adverse effects on the electrolysis process.
[0019] Preferably, the amount of hydrochloric acid (HCl) added to the chromate electrolyte is 3.03 g / L.
[0020] Preferably, the electrolysis temperature is room temperature.
[0021] Preferably, the voltage of the electrolysis is -0.79V to 1.7V.
[0022] Preferably, when the electrolytic additive is sodium oleate (NaOL), the electrolysis voltage is -0.99 to -1.7V; when the electrolytic additive is thiourea [SC(NH2)2], the electrolysis voltage is -0.84 to 1.2V; when the electrolytic additive is hydrochloric acid (HCl), the electrolysis voltage is -0.79 to -1.2V.
[0023] Since different electrolytic additives have different electrochemical activities during the electrolysis process, they have different sensitivities to voltage. Therefore, limiting the electrolysis voltage can ensure that the electrolytic additives function under appropriate conditions and avoid decomposition or failure of the additives due to excessively high or low voltages. The electrolysis voltage also affects the electrolysis window of the electrolyte, that is, the electrolyte can remain stable without decomposition within a certain voltage range. For electrolytes containing specific additives, limiting the electrolysis voltage can ensure that the electrolyte maintains a stable electrolysis state within the voltage range, avoiding the decomposition of the electrolyte to produce harmful byproducts, affecting the purity and quality of the electrolysis products. Therefore, in the electrolysis process of chromate, limiting the electrolysis voltage of different electrolytic additives effectively guarantees the rate and efficiency of the electrolysis reaction under different electrolytic additive conditions, and ensures the quality of the electrolysis products and the stability of the electrolyte.
[0024] Among them, when the electrolytic additive is sodium oleate (NaOL), the electrolytic voltage is limited to the range of -0.99 to -1.7V, ensuring that sodium oleate can play a stable role in the electrolytic process and promote the electrolytic reduction of chromate. When the electrolytic additive is thiourea [SC(NH2)2], the electrolytic voltage is limited to the range of -0.84 to 1.2V, ensuring that thiourea can effectively inhibit the precipitation of impurities during the electrolytic process and improve the purity of the electrolytic product. When the electrolytic additive is hydrochloric acid (HCl), the electrolytic voltage is limited to the range of -0.79 to -1.2V, ensuring the stability and efficiency of the electrolytic process, promoting the generation of the target product, and preventing excessive corrosion and unnecessary side reactions. The appropriate voltage range also helps to improve current efficiency and energy utilization, and reduce energy consumption and costs.
[0025] Preferably, the components of the chromate electrolyte include at least chromate, sulfuric acid and water.
[0026] Preferably, the chromate is selected from one or both of trivalent chromium salts and hexavalent chromium salts.
[0027] Preferably, the concentration of chromate in the chromate electrolyte is 250 g / L, and the concentration of sulfuric acid is 2.5 g / L.
[0028] Preferably, the electrolytic additive is introduced to reduce the energy consumption caused by the oscillation of the anode current, thereby reducing the overall energy consumption of chromate electrolysis.
[0029] Preferably, the electrolysis adopts a three-electrode system, with a Pb-Sb-Sn-Ag quaternary alloy as the working electrode, a platinum electrode as the counter electrode, and a saturated calomel electrode as the reference electrode.
[0030] Among them, since the solution of the saturated calomel electrode will be contaminated during the electrolysis process, the saturated potassium chloride solution in the saturated calomel electrode needs to be replaced after the reaction is completed.
[0031] Preferably, the working surfaces of the working electrode and the counter electrode are located in a straight line.
[0032] By cleverly designing the working surfaces of the working electrode and the counter electrode to be located in a straight line, the change in the path and the energy loss during the current transmission process are reduced, thereby improving the efficiency of the current. At the same time, the distribution of the reactants on the electrode surface is more uniform, which enhances the uniformity of the electrochemical reaction, avoids the problem of local over-reaction or under-reaction, and reduces the mechanical stress and deformation of the electrode during use, thereby improving the stability and durability of the electrode. In addition, the distance and relative position between the electrodes are more precise, which is conducive to optimizing the conditions of the electrochemical reaction and improving the reaction efficiency and product quality.
[0033] Beneficial effects of the present invention:
[0034] The method for reducing the energy consumption of chromate electrolysis of the present invention, firstly, by adding an electrolytic additive to the chromate electrolyte, the current oscillation can be effectively reduced, thereby reducing energy consumption. The technical problem of high energy consumption in the existing chromate electrolysis process for preparing metallic chromium is effectively solved. The method can improve the efficiency of electrolytic preparation of metallic chromium. Secondly, the addition of the electrolytic additive can not only reduce energy consumption, but also optimize the electrolytic conditions, so that the preparation of metallic chromium is more efficient, and the efficiency of electrolytic preparation of metallic chromium is effectively improved. Furthermore, the traditional chromate electrolysis process may produce some harmful substances, causing pollution to the environment. By introducing the electrolytic additive, the emission of harmful substances in the electrolysis process can be reduced, and the negative impact on the environment can be reduced. In summary, the method for reducing the energy consumption of chromate electrolysis of the present invention has the advantages of reducing energy consumption, improving production efficiency and environmental protection, and is of great significance for promoting the improvement and sustainable development of chromate electrolysis technology, and has promotion and application value in the field of metallurgical technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Flow chart for chromate electrolysis;
[0036] Figure 2 It is the cyclic voltammetry curve of different hydrochloric acid (HCl) concentrations;
[0037] Figure 3 It is the It curve graph when the concentration of hydrochloric acid (HCl) is 0;
[0038] Figure 4 It is a graph of the It curve when the concentration of hydrochloric acid (HCl) is 0.24 g / L;
[0039] Figure 5 It is a graph of the It curve when the concentration of hydrochloric acid (HCl) is 0.47 g / L;
[0040] Figure 6 It is a graph of the It curve when the concentration of hydrochloric acid (HCl) is 0.71 g / L;
[0041] Figure 7 It is a graph of the It curve when the concentration of hydrochloric acid (HCl) is 0.94 g / L;
[0042] Figure 8 It is the It curve graph when the concentration of hydrochloric acid (HCl) is 1.18 g / L;
[0043] Fig. 9 It is a graph of the It curve when the concentration of hydrochloric acid (HCl) is 1.42 g / L;
[0044] Fig.10 It is the It curve graph when the concentration of hydrochloric acid (HCl) is 2.00 g / L;
[0045] Fig.11 It is the It curve graph when the concentration of hydrochloric acid (HCl) is 2.60 g / L;
[0046] Fig.12 It is the It curve graph when the concentration of hydrochloric acid (HCl) is 3.03 g / L;
[0047] Fig.13 It is the It curve graph when the concentration of hydrochloric acid (HCl) is 3.78 g / L;
[0048] Fig.14 It is a partial enlarged view of the chronoamperometric (it) curves of different hydrochloric acid (HCl) concentrations;
[0049] Fig.15 is the cyclic voltammetry curve of different sodium oleate (NaOL) concentrations;
[0050] Fig.16 It is the It curve when the concentration of sodium oleate (NaOL) is 0;
[0051] Fig.17 It is the It curve graph when the concentration of sodium oleate (NaOL) is 13 mg / L;
[0052] Fig.18 It is the It curve graph when the concentration of sodium oleate (NaOL) is 26.5 mg / L;
[0053] Fig.19 It is the It curve graph when the concentration of sodium oleate (NaOL) is 82 mg / L;
[0054] Fig. 20 It is the It curve graph when the concentration of sodium oleate (NaOL) is 130 mg / L;
[0055] Fig.21 It is the It curve graph when the concentration of sodium oleate (NaOL) is 170 mg / L;
[0056] Fig. 22 It is the It curve graph when the concentration of sodium oleate (NaOL) is 200 mg / L;
[0057] Fig.23 It is a partial enlarged view of the chronoamperometric (it) curves of different sodium oleate (NaOL) concentrations;
[0058] Fig.24 Cyclic voltammetry curves of different thiourea [SC(NH2)2] concentrations;
[0059] Fig.25 It is the It curve when the concentration of thiourea [SC(NH2)2] is 0;
[0060] Fig.26It is the It curve when the concentration of thiourea [SC(NH2)2] is 18 mg / L;
[0061] Fig. 27 It is the It curve when the concentration of thiourea [SC(NH2)2] is 34 mg / L;
[0062] Fig.28 It is the It curve when the concentration of thiourea [SC(NH2)2] is 100 mg / L;
[0063] Fig.29 It is the It curve when the concentration of thiourea [SC(NH2)2] is 145 mg / L;
[0064] Fig.30 It is a partial enlarged view of the chronoamperometric (it) curves of different thiourea [SC(NH2)2] concentrations;
[0065] Fig.31 This is a cyclic voltammetry curve corresponding to adding two electrolytic additives simultaneously in Example 4;
[0066] Fig.32 This is a cyclic voltammetry curve corresponding to adding two electrolytic additives simultaneously in Example 5;
[0067] Fig.33 This is a cyclic voltammetry curve corresponding to adding two electrolytic additives simultaneously in Example 6;
[0068] Fig.34 It curve diagram corresponding to adding two electrolytic additives simultaneously in Example 4;
[0069] Fig.35 It is a graph of the It curve obtained by adding two electrolytic additives simultaneously in Example 5;
[0070] Fig.36 It curve diagram corresponding to the addition of two electrolytic additives in Example 6;
[0071] Fig.37 This is a partial enlarged view of the It curve corresponding to the addition of two electrolytic additives in Example 4;
[0072] Fig.38 This is a partial enlarged view of the It curve corresponding to the addition of two electrolytic additives in Example 5;
[0073] Fig.39 This is a partial enlarged view of the It curve corresponding to the addition of two electrolytic additives in Example 6;
[0074] Fig.40is the maximum Lyapunov exponent at different HCl concentrations;
[0075] Fig.41 is the maximum Lyapunov exponent at different sodium oleate concentrations;
[0076] Fig.42 is the maximum Lyapunov exponent at different thiourea concentrations;
[0077] Fig.43 is the relative additional power consumption caused by current oscillation under different HCl concentration systems;
[0078] Fig.44 is the relative additional power consumption caused by current oscillation under different NaOL concentration systems;
[0079] Fig.45 is the relative additional power consumption caused by current oscillation in different thiourea concentration systems;
[0080] Fig.46 It is the relative additional power consumption caused by current oscillation in the system of adding two electrolytic additives at the same time. DETAILED DESCRIPTION
[0081] The following will describe the embodiments of the present invention with reference to the preferred embodiments, and those skilled in the art can clearly understand other advantages and effects of the present invention from the contents described in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.
[0082] Example 1
[0083] like Figure 1 As shown, a method for reducing the energy consumption of chromate electrolysis comprises the following steps:
[0084] S1. Preparation of working electrode: First, the quaternary alloy (Pb-Sb-Sn-Ag) material was cut and polished to finally be made into a cylindrical shape (d>1cm 2 ; h = 5mm), the sample support (made of polyvinylidene fluoride) was loaded and used as the working electrode, the working area s = 1cm 2 Before electrolysis, the quaternary alloy electrode material was polished with 800-mesh sandpaper, soaked in anhydrous ethanol for 5 minutes, and then ultrasonically cleaned with deionized water, and dried in an oven to prepare a working electrode for standby use;
[0085] S2. Preparation of electrolyte: 50 g of chromium trioxide (CrO3) was placed in a container, 200 mL of deionized water was added, 40 μL, 80 μL, 120 μL, 160 μL, 200 μL, 240 μL, 340 μL, 440 μL, 510 μL and 640 μL of electrolytic additive hydrochloric acid (HCl) were added respectively, and then 273 μL of sulfuric acid was added, and the mixture was stirred thoroughly to evenly mix the components, thereby preparing electrolytes with different compositions for subsequent use;
[0086] S3. Build a three-electrode system: Assemble the electrochemical workstation, connect it to a computer, pour the electrolyte into the electrolytic cell, immerse the working electrode (Pb-Sb-Sn-Ag quaternary alloy), the counter electrode (platinum electrode), and the reference electrode (saturated calomel electrode) in the electrolyte at room temperature, and keep the working surfaces of the working electrode and the counter electrode in a straight line;
[0087] S4. Electrolysis: Electrolysis test was performed using CHI660E electrochemical workstation. Cyclic voltammetry test was performed on electrolytes of different compositions using the electrochemical workstation. The scanning voltage was -2 to 1 V, the scanning speed was 0.1 V / s, the sampling interval was 0.001 V, the standing time was 2 s, and the number of scanning segments was 2. Chronoamperometry test was also performed on electrolytes of different compositions using the electrochemical workstation. The voltage test range was -2 to 1 V, the scanning time was 3600 s, and the sensitivity was 1.0e-001.
[0088] Example 2
[0089] like Figure 1 As shown, a method for reducing the energy consumption of chromate electrolysis comprises the following steps:
[0090] S1. Preparation of working electrode: First, the quaternary alloy (Pb-Sb-Sn-Ag) material was cut and polished to finally be made into a cylindrical shape (d>1cm 2 ; h = 5mm), the sample support (made of polyvinylidene fluoride) was loaded and used as the working electrode, the working area s = 1cm 2 Before electrolysis, the quaternary alloy electrode material was polished with 800-mesh sandpaper, soaked in anhydrous ethanol for 5 minutes, and then ultrasonically cleaned with deionized water, and dried in an oven to prepare a working electrode for standby use;
[0091] S2. Preparation of electrolyte: 50 g of chromium trioxide (CrO3) was placed in a container, 200 mL of deionized water was added, 2.6 mg, 5.12 mg, 16.4 mg, 26 mg and 34 mg of sodium oleate (NaOL), an electrolytic additive, were added respectively, and then 273 μL of sulfuric acid was added, and the mixture was stirred thoroughly to uniformly mix the components, thereby preparing electrolytes with different compositions for subsequent use;
[0092] S3. Build a three-electrode system: Assemble the electrochemical workstation, connect it to a computer, pour the electrolyte into the electrolytic cell, immerse the working electrode (Pb-Sb-Sn-Ag quaternary alloy), the counter electrode (platinum electrode), and the reference electrode (saturated calomel electrode) in the electrolyte at room temperature, and keep the working surfaces of the working electrode and the counter electrode in a straight line;
[0093] S4. Electrolysis: Electrolysis test was performed using CHI660E electrochemical workstation. Cyclic voltammetry test was performed on electrolytes of different compositions using the electrochemical workstation. The scanning voltage was -2 to 1 V, the scanning speed was 0.1 V / s, the sampling interval was 0.001 V, the standing time was 2 s, and the number of scanning segments was 2. Chronoamperometry test was also performed on electrolytes of different compositions using the electrochemical workstation. The voltage test range was -2 to 1 V, the scanning time was 3600 s, and the sensitivity was 1.0e-001.
[0094] Example 3
[0095] like Figure 1 As shown, a method for reducing the energy consumption of chromate electrolysis comprises the following steps:
[0096] S1. Preparation of working electrode: First, the quaternary alloy (Pb-Sb-Sn-Ag) material was cut and polished to finally be made into a cylindrical shape (d>1cm 2 ; h = 5mm), the sample support (made of polyvinylidene fluoride) was loaded and used as the working electrode, the working area s = 1cm 2 Before electrolysis, the quaternary alloy electrode material was polished with 800-mesh sandpaper, soaked in anhydrous ethanol for 5 minutes, and then ultrasonically cleaned with deionized water, and dried in an oven to prepare a working electrode for standby use;
[0097] S2. Preparation of electrolyte: 50 g of chromium trioxide (CrO3) was placed in a container, 200 mL of deionized water was added, 3.6 mg, 6.8 mg, 20 mg and 29 mg of electrolytic additive thiourea [SC(NH2)2] were added respectively, and then 273 μL of sulfuric acid was added, and the mixture was stirred thoroughly to uniformly mix the components, thereby preparing electrolytes with different compositions for subsequent use;
[0098] S3. Build a three-electrode system: Assemble the electrochemical workstation, connect it to a computer, pour the electrolyte into the electrolytic cell, immerse the working electrode (Pb-Sb-Sn-Ag quaternary alloy), the counter electrode (platinum electrode), and the reference electrode (saturated calomel electrode) in the electrolyte at room temperature, and keep the working surfaces of the working electrode and the counter electrode in a straight line;
[0099] S4. Electrolysis: Electrolysis test was performed using CHI660E electrochemical workstation. Cyclic voltammetry test was performed on electrolytes of different compositions using the electrochemical workstation. The scanning voltage was -2 to 1 V, the scanning speed was 0.1 V / s, the sampling interval was 0.001 V, the standing time was 2 s, and the number of scanning segments was 2. Chronoamperometry test was also performed on electrolytes of different compositions using the electrochemical workstation. The voltage test range was -2 to 1 V, the scanning time was 3600 s, and the sensitivity was 1.0e-001.
[0100] Example 4
[0101] like Figure 1 As shown, a method for reducing the energy consumption of chromate electrolysis comprises the following steps:
[0102] S1. Preparation of working electrode: First, the quaternary alloy (Pb-Sb-Sn-Ag) material was cut and polished to finally be made into a cylindrical shape (d>1cm 2 ; h = 5mm), the sample support (made of polyvinylidene fluoride) was loaded and used as the working electrode, the working area s = 1cm 2 Before electrolysis, the quaternary alloy electrode material was polished with 800-mesh sandpaper, soaked in anhydrous ethanol for 5 minutes, and then ultrasonically cleaned with deionized water, and dried in an oven to prepare a working electrode for standby use;
[0103] S2. Preparation of electrolyte: 50 g of chromium trioxide (CrO3) is placed in a container, 200 mL of deionized water is added, hydrochloric acid and thiourea [SC(NH2)2] are added as electrolytic additives, and then 273 μL of sulfuric acid is added, and the mixture is stirred thoroughly to uniformly mix the components, thereby preparing an electrolyte for subsequent use; wherein the concentration of hydrochloric acid in the prepared electrolyte is 2.27 g / L, and the concentration of thiourea is 340 mg / L;
[0104] S3. Build a three-electrode system: Assemble the electrochemical workstation, connect it to a computer, pour the electrolyte into the electrolytic cell, immerse the working electrode (Pb-Sb-Sn-Ag quaternary alloy), the counter electrode (platinum electrode), and the reference electrode (saturated calomel electrode) in the electrolyte at room temperature, and keep the working surfaces of the working electrode and the counter electrode in a straight line;
[0105] S4. Electrolysis: Electrolysis test was performed using CHI660E electrochemical workstation. Cyclic voltammetry test was performed on electrolytes of different compositions using the electrochemical workstation. The scanning voltage was -2 to 1 V, the scanning speed was 0.1 V / s, the sampling interval was 0.001 V, the standing time was 2 s, and the number of scanning segments was 2. Chronoamperometry test was also performed on electrolytes of different compositions using the electrochemical workstation. The voltage test range was -2 to 1 V, the scanning time was 3600 s, and the sensitivity was 1.0e-001.
[0106] Example 5
[0107] like Figure 1 As shown, a method for reducing the energy consumption of chromate electrolysis comprises the following steps:
[0108] S1. Preparation of working electrode: First, the quaternary alloy (Pb-Sb-Sn-Ag) material was cut and polished to finally be made into a cylindrical shape (d>1cm 2 ; h = 5mm), the sample support (made of polyvinylidene fluoride) was loaded and used as the working electrode, the working area s = 1cm 2 Before electrolysis, the quaternary alloy electrode material was polished with 800-mesh sandpaper, soaked in anhydrous ethanol for 5 minutes, and then ultrasonically cleaned with deionized water, and dried in an oven to prepare a working electrode for standby use;
[0109] S2. Preparation of electrolyte: 50 g of chromium trioxide (CrO3) was placed in a container, 200 mL of deionized water was added, hydrochloric acid and sodium oleate (NaOL) were added as electrolytic additives, and then 273 μL of sulfuric acid was added, and the mixture was stirred thoroughly to uniformly mix the components, thereby preparing electrolytes with different components for subsequent use; wherein the concentration of hydrochloric acid in the prepared electrolyte was 2.27 g / L, and the concentration of sodium oleate was 150 mg / L;
[0110] S3. Build a three-electrode system: Assemble the electrochemical workstation, connect it to a computer, pour the electrolyte into the electrolytic cell, immerse the working electrode (Pb-Sb-Sn-Ag quaternary alloy), the counter electrode (platinum electrode), and the reference electrode (saturated calomel electrode) in the electrolyte at room temperature, and keep the working surfaces of the working electrode and the counter electrode in a straight line;
[0111] S4. Electrolysis: Electrolysis test was performed using CHI660E electrochemical workstation. Cyclic voltammetry test was performed on electrolytes of different compositions using the electrochemical workstation. The scanning voltage was -2 to 1 V, the scanning speed was 0.1 V / s, the sampling interval was 0.001 V, the standing time was 2 s, and the number of scanning segments was 2. Chronoamperometry test was also performed on electrolytes of different compositions using the electrochemical workstation. The voltage test range was -2 to 1 V, the scanning time was 3600 s, and the sensitivity was 1.0e-001.
[0112] Example 6
[0113] like Figure 1 As shown, a method for reducing the energy consumption of chromate electrolysis comprises the following steps:
[0114] S1. Preparation of working electrode: First, the quaternary alloy (Pb-Sb-Sn-Ag) material was cut and polished to finally be made into a cylindrical shape (d>1cm 2 ; h = 5mm), the sample support (made of polyvinylidene fluoride) was loaded and used as the working electrode, the working area s = 1cm 2 Before electrolysis, the quaternary alloy electrode material was polished with 800-mesh sandpaper, soaked in anhydrous ethanol for 5 minutes, and then ultrasonically cleaned with deionized water, and dried in an oven to prepare a working electrode for standby use;
[0115] S2. Preparation of electrolyte: 50 g of chromium trioxide (CrO3) was placed in a container, 200 mL of deionized water was added, thiourea [SC(NH2)2] and sodium oleate (NaOL) were added as electrolytic additives, and then 273 μL of sulfuric acid was added, and the mixture was stirred thoroughly to uniformly mix the components, thereby preparing electrolytes with different components for subsequent use; wherein the concentration of thiourea in the prepared electrolyte was 340 mg / L, and the concentration of sodium oleate was 150 mg / L;
[0116] S3. Build a three-electrode system: Assemble the electrochemical workstation, connect it to a computer, pour the electrolyte into the electrolytic cell, immerse the working electrode (Pb-Sb-Sn-Ag quaternary alloy), the counter electrode (platinum electrode), and the reference electrode (saturated calomel electrode) in the electrolyte at room temperature, and keep the working surfaces of the working electrode and the counter electrode in a straight line;
[0117] S4. Electrolysis: Electrolysis test was performed using CHI660E electrochemical workstation. Cyclic voltammetry test was performed on electrolytes of different compositions using the electrochemical workstation. The scanning voltage was -2 to 1 V, the scanning speed was 0.1 V / s, the sampling interval was 0.001 V, the standing time was 2 s, and the number of scanning segments was 2. Chronoamperometry test was also performed on electrolytes of different compositions using the electrochemical workstation. The voltage test range was -2 to 1 V, the scanning time was 3600 s, and the sensitivity was 1.0e-001.
[0118] Comparative Example 1
[0119] A conventional chromate electrolysis method comprises the following steps:
[0120] S1. Preparation of working electrode: First, the quaternary alloy (Pb-Sb-Sn-Ag) material was cut and polished to finally be made into a cylindrical shape (d>1cm 2 ; h = 5mm), the sample support (made of polyvinylidene fluoride) was loaded and used as the working electrode, the working area s = 1cm 2 Before electrolysis, the quaternary alloy electrode material was polished with 800-mesh sandpaper, soaked in anhydrous ethanol for 5 minutes, and then ultrasonically cleaned with deionized water, and dried in an oven to prepare a working electrode for standby use;
[0121] S2. Preparation of electrolyte: 50 g of chromium trioxide (CrO3) is placed in a container, 200 mL of deionized water is added, and then 273 μL of sulfuric acid is added, and the mixture is stirred thoroughly to uniformly mix the components, thereby preparing electrolytes with different components for subsequent use;
[0122] S3. Build a three-electrode system: Assemble the electrochemical workstation, connect it to a computer, pour the electrolyte into the electrolytic cell, immerse the working electrode (Pb-Sb-Sn-Ag quaternary alloy), the counter electrode (platinum electrode), and the reference electrode (saturated calomel electrode) into the electrolyte, and keep the working surfaces of the working electrode and the counter electrode in a straight line;
[0123] S4. Electrolysis: Electrolysis test was performed using CHI660E electrochemical workstation. Cyclic voltammetry test was performed on electrolytes of different compositions using the electrochemical workstation. The scanning voltage was -2 to 1 V, the scanning speed was 0.1 V / s, the sampling interval was 0.001 V, the standing time was 2 s, and the number of scanning segments was 2. Chronoamperometry test was also performed on electrolytes of different compositions using the electrochemical workstation. The voltage test range was -2 to 1 V, the scanning time was 3600 s, and the sensitivity was 1.0e-001.
[0124] Detection and analysis
[0125] 1) Cyclic voltammetry and chronoamperometric testing
[0126] The cyclic voltammetry curves corresponding to different hydrochloric acid (HCl) concentrations in Example 1 and Comparative Example 1 are as follows: Figure 2 The It curves corresponding to different hydrochloric acid (HCl) concentrations in Example 1 and Comparative Example 1 are shown in FIG. Figures 3 to 14 shown.
[0127] Figure 2 a corresponds to the cyclic voltammetry curve of the comparative example 1 in which the amount of hydrochloric acid (HCl) added is 0; Figure 2 b~ Figure 2 k respectively correspond to the cyclic voltammetry curves of hydrochloric acid (HCl) added in amounts of 40 μL, 80 μL, 120 μL, 160 μL, 200 μL, 240 μL, 340 μL, 440 μL, 510 μL and 640 μL in Example 1.
[0128] Figure 3 It curve corresponding to the comparison example 1 in which the amount of hydrochloric acid (HCl) added is 0; Figures 4 to 13 The It curves correspond to the addition amounts of hydrochloric acid (HCl) of 40 μL, 80 μL, 120 μL, 160 μL, 200 μL, 240 μL, 340 μL, 440 μL, 510 μL and 640 μL in Example 1, respectively. Fig.14 This is a partial enlarged view of the chronoamperometric (it) curve under different hydrochloric acid concentrations.
[0129] from Figure 2 From the comparative analysis, it can be seen that there are obvious cross-rings in the cyclic voltammetry test curves under different HCl concentration systems, proving that there is current oscillation in the system. With the increase of HCl concentration, the potential interval of cross-ring in the cyclic voltammetry test curve shifts from [-0.83~-0.92]V to [-1.17~-1.47]V, indicating that the concentration of HCl has a certain influence on the reaction on the surface of the anode electrode, thus causing the anode current oscillation potential interval to change.
[0130] from Figures 3 to 13 In, and Fig.14 From the comparative analysis, we can see that the chronoamperometric test results show that different HCl concentration systems have different amplitudes, which proves that different HCl concentrations will produce different current oscillation effects. Compared with the system without HCl added, the current amplitude is significantly reduced after adding HCl, which further proves that the addition of electrolytic additives effectively alleviates the current oscillation.
[0131] The cyclic voltammetry curves corresponding to different sodium oleate (NaOL) concentrations in Example 2 and Comparative Example 1 are as follows: Fig.15 shown.
[0132] The It curves corresponding to different sodium oleate (NaOL) concentrations in Example 2 and Comparative Example 1 are as follows: Figures 16 to 23 shown.
[0133] Fig.15 a corresponds to the cyclic voltammetry curve of the comparative example 1 in which the addition amount of sodium oleate (NaOL) is 0; Fig.15 b~ Fig.15 g respectively correspond to the cyclic voltammetry curves of Example 2 when the addition amounts of sodium oleate (NaOL) are 2.6 mg, 5.12 mg, 16.4 mg, 26 mg, 34 mg and 40 mg.
[0134] Fig.16 It curve corresponding to the addition amount of sodium oleate (NaOL) in Control Example 1 is 0; Figure 17 to Figure 22 They correspond to the It curves of Example 2 in which the addition amounts of sodium oleate (NaOL) are 2.6 mg, 5.12 mg, 16.4 mg, 26 mg, 34 mg and 40 mg, respectively. Fig.23 This is a partial enlarged view of the chronoamperometric (it) curve at different sodium oleate (NaOL) concentrations.
[0135] from Fig.15 From the comparative analysis, it can be seen that there are obvious cross-rings in the cyclic voltammetry test results under different NaOL concentration systems, indicating that there are current oscillations in the system. When the NaOL concentration is 0mg / L, 13mg / L, 25.6mg / L, 82mg / L, 130mg / L, and 170mg / L, there is obvious nonlinear current feedback, and when the NaOL concentration is 100mg / L and 200mg / L, there is no obvious current feedback. And after adding sodium oleate, the current oscillation potential interval shifts negatively. When NaOL is not added, the oscillation interval of the cyclic voltammetry curve is [-0.8~-0.86]V, and after adding NaOL, the oscillation interval shifts negatively to [-0.1~-1.4]V. This shows that the addition of NaOL has a certain effect on the reaction of the anode electrode, resulting in a change in the potential interval of the current oscillation.
[0136] from Figures 16 to 22 In, and Fig.23 From the comparative analysis, it can be seen that the results of the chronoamperometric test show that different sodium oleate (NaOL) concentration systems have different amplitudes, which proves that different sodium oleate (NaOL) concentrations will produce different current oscillation effects. Compared with the system without adding sodium oleate (NaOL), the current amplitude is significantly reduced after adding sodium oleate (NaOL), which further proves that the addition of electrolytic additives effectively alleviates the current oscillation.
[0137] The cyclic voltammetry curves corresponding to different thiourea [SC(NH2)2] concentrations in Example 3 and Comparative Example 1 are as follows: Fig.24 The It curves corresponding to different thiourea [SC(NH2)2] concentrations in Example 3 and Comparative Example 1 are shown in FIG. Figures 25 to 30 shown.
[0138] Fig.24 a corresponds to the cyclic voltammetry curve of the comparative example 1 in which the amount of thiourea [SC(NH2)2] added is 0; Fig.24 b~ Fig.24 e respectively correspond to the cyclic voltammetry curves of Example 3 when the addition amounts of sodium oleate (NaOL) are 3.6 mg, 6.8 mg, 20 mg and 29 mg.
[0139] Fig.25 It curve corresponding to the addition amount of sodium oleate (NaOL) in Control Example 1 is 0; Figure 26 to Figure 29 These correspond to the It curves in Example 2 when the addition amounts of sodium oleate (NaOL) are 2.6 mg, 5.12 mg, 16.4 mg, 26 mg and 34 mg, respectively. Fig.30 This is a partial enlarged view of the chronoamperometric (it) curve at different sodium oleate (NaOL) concentrations.
[0140] from Fig.24 From the comparative analysis, it can be seen that in the cyclic voltammetry test results under different thiourea concentration systems, obvious cross-rings can be seen, indicating that there is current oscillation in the system. Obvious nonlinear current feedback appeared when the thiourea concentration was 18mg / L and 145mg / L, and there was no obvious current feedback when the thiourea concentration was 34mg / L and 100mg / L.
[0141] from Figure 25 to Figure 29 In, and Fig.30 From the comparative analysis, it can be seen that the results of the chronoamperometric test show that different thiourea concentration systems have different amplitudes, which proves that different thiourea concentrations will produce different current oscillation effects. Compared with the system without thiourea added, the current amplitude is significantly reduced after adding thiourea, which further proves that the addition of electrolytic additives effectively alleviates the current oscillation.
[0142] The cyclic voltammetry curves corresponding to the addition of two electrolytic additives in Examples 4 to 6 are as follows: Figure 31 to Figure 33 The It curves corresponding to the addition of two electrolytic additives in Examples 4 to 6 are shown in FIG. Figure 34 to Figure 36 The partial enlarged diagram of the It curve corresponding to the addition of two electrolytic additives in Examples 4 to 6 is shown in FIG. Figure 37 to Figure 39 shown.
[0143] from Figure 31 to Figure 33From the analysis, we can see that cross-rings can be seen in the cyclic voltammetry test results of systems with different electrolytic additive combinations, indicating that current oscillations exist in the system.
[0144] from Figure 34 to Figure 39 From the analysis, we can see that the results of the chronoamperometric test show that the systems with different combinations of electrolytic additives have different amplitudes, which proves that different combinations of electrolytic additives will produce different current oscillation effects. Compared with the system without adding electrolytic additives, the current amplitude is significantly reduced after adding electrolytic additives, which further proves that the addition of electrolytic additives effectively alleviates the current oscillation.
[0145] 2) Maximum Lyapunov exponent
[0146] Among them, the basic characteristic of chaotic motion is that the motion is extremely sensitive to the initial conditions. In the dynamic system, the Lyapunov index is the orbit generated by two very close initial values, and the amount of this phenomenon is separated exponentially over time. The Lyapunov index provides a feasible estimate and prediction for the stability of nonlinear systems, and has guiding significance for the adaptive control and synchronization methods of chaos. For a general n-dimensional dynamic system, the Lyapunov index is defined as follows: Let F be R n -R n The n-dimensional mapping on determines an n-dimensional discrete dynamic system.
[0147] X n+1 =F(X n )
[0148] The initial condition of the system is an infinitesimal n-dimensional sphere. Due to the natural deformation during the evolution process, the sphere will become an ellipsoid. Arrange all the principal axes of the ellipsoid in order of their lengths, then the i-th Lyapunov index is calculated according to the length P of the i-th principal axis. i The rate of increase of (n) is defined as:
[0149]
[0150] Thus, the Lyapunov index is related to the contraction or expansion of the trajectory in phase space. In the direction where the Lyapunov index is less than zero, the trajectory contracts, the motion is stable, and it is insensitive to the initial conditions; while in the direction where the Lyapunov index is positive, the trajectory separates rapidly and is sensitive to the initial conditions. Note that the length of the major axis of the ellipsoid is Increase, the area defined by the first two principal axes is Increase, the volume defined by the first three principal axes is Increase, and so on. That is, the sum of the first j exponents of the Lyapunov exponent is determined by the long-term average rate of increase of the j-dimensional volume exponent defined by the first j principal axes. Usually, all Lyapunov exponent spectra are arranged by size as follows:
[0151] λ1≥λ2≥λ3≥…>λ n
[0152] The positive or negative nature of the Lyapunov exponent λ can be used to determine whether there is chaotic motion in a nonlinear system. One-dimensional case: When λ1<0, it means that there is an attractor and it can only be a fixed point. When λ1>0, it means that the system must be chaotic motion.
[0153] The maximum Lyapunov exponent results of the systems in Example 1 and Comparative Example 1 are as follows: Fig.40 The maximum Lyapunov exponent results of the systems in Example 2 and Comparative Example 1 are shown in Fig.41 The maximum Lyapunov exponent results of the systems in Example 3 and Comparative Example 1 are shown in Fig.42 shown.
[0154] from Fig.40 It can be seen from the analysis that the introduction of hydrochloric acid as an electrolytic additive into the chromate system has a significant effect on the kinetic characteristics and energy consumption of the system. And as the concentration of hydrochloric acid gradually increases, the maximum Lyapunov index of the system shows a "wave-like" fluctuation law. In the entire concentration change range, the maximum Lyapunov index at each concentration is lower than the initial value of the system without adding hydrochloric acid, which proves that the intervention of hydrochloric acid effectively suppresses the chaotic characteristics of the system. Among them, when the concentration of hydrochloric acid reaches 3.03g / L, the maximum Lyapunov index of the system drops to the minimum value of 0.0014. According to the positive correlation between the maximum Lyapunov index and the degree of chaos, that is, the larger the index, the more significant the chaotic characteristics and the higher the degree of chaos. It can be determined that the degree of chaos of the system at this concentration is at the lowest level.
[0155] from Fig.41It can be seen from the analysis that the introduction of sodium oleate as an electrolytic additive into the chromate system has a significant effect on the kinetic characteristics and energy consumption of the system. And with the gradual increase of the sodium oleate concentration, the maximum Lyapunov index of the system shows a trend of first rising and then falling. In the entire concentration change process, the maximum Lyapunov index corresponding to each concentration is lower than the value of the original system without sodium oleate, which proves that the addition of sodium oleate effectively weakens the chaotic performance of the system. When the sodium oleate concentration reaches 200 mg / L, the maximum Lyapunov index of the system drops to the minimum value of 0.0013. Given that there is a positive correlation between the maximum Lyapunov index and the chaotic characteristics and the degree of chaos, that is, the larger the index, the more significant the chaotic characteristics and the higher the degree of chaos, it can be clearly seen that the degree of chaos of the system is at its lowest state at a concentration of 200 mg / L.
[0156] from Fig.42 It can be seen from the analysis that the introduction of thiourea as an electrolytic additive into the chromate system has a significant effect on the kinetic characteristics and energy consumption of the system. And as the concentration of thiourea gradually increases, its maximum Lyapunov index shows a change characteristic of first decreasing, then increasing, and then decreasing. In the entire concentration change range, the maximum Lyapunov index corresponding to each concentration is lower than the corresponding value of the system without adding thiourea, which proves that the addition of thiourea effectively suppresses the chaotic characteristics of the system. When the thiourea concentration reaches 34 mg / L, the maximum Lyapunov index of the system reaches the lowest value of 0.0026. In view of the close positive correlation between the maximum Lyapunov index and the chaotic characteristics and the degree of chaos, that is, the larger the index, the more prominent the chaotic characteristics and the higher the degree of chaos, so it can be determined that under the specific condition of thiourea concentration of 34 mg / L, the degree of chaos of the system is at the minimum state.
[0157] 3) Relative additional power consumption caused by current oscillation
[0158] When electrochemical oscillation occurs at the anode, the power consumption caused is different because the electrochemical oscillation behavior under constant potential and constant current conditions is completely different. The current oscillation under constant potential electrolysis will increase the average current and cause additional power consumption. At this time, the method for calculating power consumption is different, which can be derived from formula (1). The current oscillation under constant potential usually fluctuates from the reference low current to the high current direction. Therefore, the reference low current is set to be, and the electrolysis power under constant potential conditions is calculated by the following formulas (2) to (3):
[0159] P=V·I (1)
[0160]
[0161]
[0162] In formulas (1) to (3), P represents power consumption, V represents voltage, I represents current, U represents constant potential, and I baseline represents the current corresponding to the baseline of the oscillation, t2 represents the time corresponding to the end of the oscillation wave selected for calculation, t1 represents the time when the oscillation wave starts, P aver Indicates the power of electrolysis, P extra The power consumption and relative additional power consumption of the electrochemical oscillation under the electrode potential are calculated according to formulas (2) and (3).
[0163] The relative additional power consumption results of the current oscillation of the systems in Example 1 and Comparative Example 1 are as follows: Fig.43 The relative additional power consumption results of the current oscillation of the system in Example 2 and Comparative Example 1 are shown in Fig.44 The relative additional power consumption results of the current oscillation of the system in Example 3 and Comparative Example 1 are shown in Fig.45 shown.
[0164] from Fig.43 It can be seen from the analysis that the additional power consumption of the system after adding hydrochloric acid is lower than the baseline value without adding. As the concentration of hydrochloric acid increases, the additional power consumption of the electrolytic chromate system shows a gradually decreasing trend. When the concentration of hydrochloric acid is 3.03g / L, the additional power consumption reaches the lowest value of 0.062KW / h. Compared with the system without adding hydrochloric acid, the additional power consumption is reduced by as much as 93.3%.
[0165] from Fig.44 It can be seen from the analysis that the additional power consumption of the system after adding sodium oleate is lower than that without adding it. With the increase of sodium oleate concentration, the additional power consumption of the electrolytic chromate system shows a trend of gradual decrease as a whole. When the sodium oleate concentration is 200 mg / L, the additional power consumption drops to the minimum value of 0.137 KW / h. Compared with the system without adding sodium oleate, the reduction ratio of additional power consumption at this time reaches 85.9%.
[0166] from Fig.45 It can be seen from the analysis that the additional power consumption of the system after adding thiourea is lower than that without adding thiourea. In the process of thiourea concentration change, the additional power consumption of the electrolytic chromate system shows a gradual downward trend as a whole. When the thiourea concentration is 34mg / L, the additional power consumption reaches the lowest value of 0.144W / h. Compared with the system without adding thiourea, the reduction of additional power consumption at this time reaches 85.2%.
[0167] The additional power consumption caused by the oscillation of the anode current in the system with hydrochloric acid (2.27 g / L) and thiourea (340 mg / L) added in Example 4 was analyzed and accurately calculated, and a system without any additives was used as a control. The results are as follows: Fig.46 shown.
[0168] from Fig.46 From the analysis, it can be seen that the additional power consumption of the system after adding hydrochloric acid (2.27g / L) and thiourea (340mg / L) is lower than the baseline value when no electrolytic additives are added. The additional power consumption reaches 0.283KW / h. Compared with the system without adding any electrolytic additives, the additional power consumption is reduced by as much as 70.9%.
[0169] The additional power consumption caused by the oscillation of the anode current in the system with hydrochloric acid (2.27 g / L) and sodium oleate (150 mg / L) added in Example 5 was analyzed and accurately calculated, and a system without any additives was used as a control. The results are as follows: Fig.46 shown.
[0170] from Fig.46 From the analysis, it can be seen that the additional power consumption of the system after adding hydrochloric acid (2.27g / L) and sodium oleate (150mg / L) is lower than the baseline value when no electrolytic additives are added. The additional power consumption reaches 0.616KW / h. Compared with the system without adding any electrolytic additives, the additional power consumption is reduced by as much as 36.7%.
[0171] The additional power consumption caused by the oscillation of the anode current in the system with sodium oleate (150 mg / L) and thiourea (340 mg / L) added in Example 6 was analyzed and accurately calculated, and a system without any additives was used as a control. The results are as follows: Fig.46 shown.
[0172] from Fig.46 From the analysis, it can be seen that the additional power consumption of the system after adding sodium oleate (150 mg / L) and thiourea (340 mg / L) is lower than the baseline value when no electrolytic additives are added. The additional power consumption reaches 0.267 KW / h. Compared with the system without adding any electrolytic additives, the additional power consumption is reduced by as much as 72.6%.
[0173] In summary, the method of reducing the energy consumption of chromate electrolysis of the present invention, by introducing at least one of hydrochloric acid, thiourea and sodium oleate as an electrolytic additive in the chromate system, produces significant optimization effects on the system and effectively suppresses the chaos of the system. In the process of increasing the concentration of each, the additional power consumption shows a decreasing trend as a whole, which effectively demonstrates the key role of these three additives in optimizing the chromate electrolysis system and reducing the additional energy consumption caused by the oscillation of the anode current, and has the value of promotion and application in the field of metallurgical technology.
[0174] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.
Claims
1. A method for reducing energy consumption in chromate electrolysis, characterized in that: The following steps are involved: Electrolytic additives are added to the chromate electrolyte, and then metallic chromium is prepared by electrolysis. The introduction of the electrolytic additives can reduce the energy consumption caused by current oscillation, thereby reducing the overall energy consumption of chromate electrolysis.
2. The method for reducing energy consumption of chromate electrolysis according to claim 1, characterized in that: The electrolytic additive is selected from at least one of sodium oleate (NaOL), thiourea [SC(NH2)2] and hydrochloric acid (HCl).
3. The method for reducing energy consumption of chromate electrolysis according to claim 2, characterized in that: The amount of sodium oleate (NaOL) added to the chromate electrolyte is 13-200 mg / L.
4. The method for reducing energy consumption of chromate electrolysis according to claim 2, characterized in that: The added amount of thiourea [SC(NH2)2] in the chromate electrolyte is 18~350 mg / L.
5. The method for reducing energy consumption of chromate electrolysis according to claim 2, characterized in that: The amount of hydrochloric acid (HCl) added to the chromate electrolyte is 0.2-4 g / L.
6. The method for reducing energy consumption of chromate electrolysis according to claim 1, characterized in that: The voltage of the electrolysis is -0.79V~1.7V; And / or, the electrolysis temperature is room temperature; and / or, the components of the chromate electrolyte include at least chromate, sulfuric acid and water; And / or, the chromate is selected from one or both of trivalent chromium salts and hexavalent chromium salts.
7. The method for reducing energy consumption of chromate electrolysis according to claim 6, characterized in that: When the electrolytic additive is sodium oleate (NaOL), the electrolytic voltage is -0.99~-1.7V; when the electrolytic additive is thiourea [SC(NH2)2], the electrolytic voltage is -0.84~1.2V; when the electrolytic additive is hydrochloric acid (HCl), the electrolytic voltage is -0.79~-1.2V; And / or, the concentration of chromate in the chromate electrolyte is 250 g / L, and the concentration of sulfuric acid is 2.5 g / L.
8. The components of the chromate electrolyte include at least chromate, sulfuric acid and water; And / or, the chromate is selected from one or both of trivalent chromium salts and hexavalent chromium salts.
9. The method for reducing energy consumption of chromate electrolysis according to claim 1, characterized in that: The introduction of the electrolytic additive is to reduce the energy consumption caused by the oscillation of the anode current, thereby reducing the overall energy consumption of chromate electrolysis.
10. The method for reducing energy consumption of chromate electrolysis according to claim 1, characterized in that: The electrolysis adopts a three-electrode system, with a Pb-Sb-Sn-Ag quaternary alloy as a working electrode, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode.
11. The method for reducing energy consumption of chromate electrolysis according to claim 9, characterized in that: The working surfaces of the working electrode and the counter electrode are located on a straight line.